2016
DOI: 10.1039/c5gc01008j
|View full text |Cite|
|
Sign up to set email alerts
|

CHEM21 selection guide of classical- and less classical-solvents

Abstract: ARTICLEThis journal is ABSTRACT: A selection guide of common solvents has been elaborated, based on a survey of publically available solvent selection guides. In order to rank less classical solvents, a set of Safety, Health and Environment criteria is proposed, aligned with the Global Harmonized System (GHS) and European regulations. A methodology based on a simple combination of these criteria gives an overall preliminary ranking of any solvent. This enables in particular a simplified greenness evaluation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
1,506
0
24

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,585 publications
(1,541 citation statements)
references
References 48 publications
11
1,506
0
24
Order By: Relevance
“…The ACS Green Chemistry Institute-Pharmaceutical Roundtable (ACS GCI-PR) has made available a more general list, developed collaboratively by the members of different pharmaceutical companies, 2 and a comparison between individual solvent guides has been published by the Chem21 consortium. 8,9 Water is always at the top in the lists of green solvents, and much work has been carried out on transition metal-catalysed reactions in this solvent. [10][11][12][13][14] However, the physical properties of water do not always make it practically the best solvent for an industrial process, 6 and the low solubility of many organic compounds in water represents an obvious issue.…”
Section: Introductionmentioning
confidence: 99%
“…The ACS Green Chemistry Institute-Pharmaceutical Roundtable (ACS GCI-PR) has made available a more general list, developed collaboratively by the members of different pharmaceutical companies, 2 and a comparison between individual solvent guides has been published by the Chem21 consortium. 8,9 Water is always at the top in the lists of green solvents, and much work has been carried out on transition metal-catalysed reactions in this solvent. [10][11][12][13][14] However, the physical properties of water do not always make it practically the best solvent for an industrial process, 6 and the low solubility of many organic compounds in water represents an obvious issue.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently focused our main interest towards polar aprotic solvents that are of major concern in terms of safety and toxicity [6] but that are also extremely useful for performing modern synthetic transformations specifically in the case of cross-coupling reactions and C-H functionalizations.…”
Section: Solvent/reaction Mediummentioning
confidence: 99%
“…It is therefore obvious that major attention must be devoted to the selection of the most adequate solvents to achieve the highest chemical efficiency but also to avoid the use of most problematic and widely used traditional reaction media that derive from non-renewable fossil resources and that features high toxicity and bio-accumulation potential [4][5][6][7][8][9].…”
Section: Solvent/reaction Mediummentioning
confidence: 99%
“…A screen of potential activating agents in THF (Table 1, Entries 1-6) revealed that both PyBroP and TsCl were competent reaction partners, with the former showing modest C2 selectivity and the latter a higher level of selectivity in favour of the C4 isomer. Mindful that THF is regarded as problematic in industrially-led analyses of solvents, 23 we screened a variety of more favourable solvents in conjunction with TsCl (Entries 7-12). Pleasingly, a comparable yield to that achieved in THF was obtained using ethyl acetate (a 'recommended' solvent 23 ), albeit with a slightly reduced regioselectivity (Entry 8).…”
mentioning
confidence: 99%
“…Mindful that THF is regarded as problematic in industrially-led analyses of solvents, 23 we screened a variety of more favourable solvents in conjunction with TsCl (Entries 7-12). Pleasingly, a comparable yield to that achieved in THF was obtained using ethyl acetate (a 'recommended' solvent 23 ), albeit with a slightly reduced regioselectivity (Entry 8). Additionally, the charge of triethylamine base could also be reduced to two equivalents versus the Noxide/activating agent without detriment.…”
mentioning
confidence: 99%